Pengaruh Social Media Marketing terhadap Brand Awareness, Brand Image dan Brand Loyalty Pesona Indonesia - Swimbawa, Made Krisnantha; M. Lemy, Diena (Bulletin of Community Engagement, 2023)
This research aims to investigate the influence of Social Media Marketing (SMM) on Brand Awareness, Brand Image and Brand Loyalty of Pesona Indonesia. Quantitative methods with regression analysis were used to analyze data obtained from respondents involved in the use of social media related to Pesona Indonesia. Data collection was carried out through questionnaires distributed online to respondents who had interacted with Pesona Indonesia content on various social media platforms. The independent variables in this research are marketing activities on social media such as the number of posts, interactions and type of content shared. Meanwhile, the dependent variable consists of Brand Awareness, Brand Image, and Brand Loyalty which are measured through questions related to the respondents' awareness, perception, and level of loyalty to the Pesona Indonesia brand. The results of the regression analysis show that there is a significant positive influence between the use of Social Media Marketing and Brand Awareness, Brand Image and Brand Loyalty of Pesona Indonesia. It was found that the more active Pesona Indonesia was in interacting and sharing content on social media, the higher the level of consumer awareness, perception and loyalty towards the brand. This research provides an important contribution in understanding the role of Social Media Marketing in influencing brand image, awareness and consumer loyalty towards Pesona Indonesia. The practical implications of this research can help brand managers to plan more effective marketing strategies on social media platforms to increase consumer awareness, image and loyalty to the Pesona Indonesia brand. Keywords: Social Media Marketing, Brand Awareness, Brand Image, Brand Loyalty